Adsorptive Treatment of Azo Dyes from Aqueous Solution Using PVA Coated Carbon Black as An Adsorbent - Gehlot, Poonam; Daga, Kailash; Pallavi, V. (Asian Journal of Chemistry, 2010)
The paper concerns with the adsorptive treatment of dye 1-brilliant yellow and dye 2-benzoazurin G in aqueous solution on polyvinyl alcohol (PVA) coated carbon black as an adsorbent. The effect of pH, concentration and time on adsorption process was investigated and adsorption equilibrium isotherms reported. The adsorption equilibrium data fitted to both Freundlich and Langmuir isotherms equally well. Batch adsorption studies were conducted at room temperature (30 ºC). The per cent removal of benzoazurin G was 80 % and brilliant yellow was 84 %.